HIGHER SCHOOL TEACHERS’ DIGITAL COMPETENCE: STRATEGIES FOR SELF-ASSESSMENT AND IMPROVEMENT - Malykhin, Oleksandr; Aristova, Nataliia; Kovalchuk, Vasyl; Opaliuk, Tetiana; Yarmolchuk, Taras (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The paper was aimed at examining higher school teachers’ strategies for self-assessing and improving digital competence and finding out the range of the most effective and innovative ones. The research sample consisted of 115 higher school teachers from four higher educational establishments in Ukraine. The research sample was selected with the use of a non-random sampling technique. Personal data of research sample were taken into consideration i.e. demography, gender balance, age and specialty. The research strategy for collecting empirical data combined a web-based questionnaire, individual interviews, conversations with respondents and analysis of reflexive texts. The collected empirical data were then analyzed both quantitatively and qualitatively. The data were processed by means of Microsoft Excel 2016 and verified by Chronbach’ Alfa (An Index of Reliability). During the development of a web-based questionnaire the authors defined seven cognitive content-components of higher school teachers’ digital competence and each of them was given a synthetic index. The obtained findings showed that higher school teachers had different levels of digital competence: ranging from low to high, and revealed the diversity in peculiarities of its manifestations and ways of thinking when operating the competence mentioned. The research results served as the basis for offering innovative strategies for self-assessing and improving higher school teachers’ digital competence.